Endoscopic sleeve gastroplasty for obesity: A multicenter study of 248 patients with 24 months follow-up - Emel Ahıshalı, (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Ahıshalı E. Endoscopic sleeve gastroplasty for obesity: A multicenter study of 248 patients with 24 months follow-up. Turk J Gastroenterol 2018; 29: 373-4.